Influence of Cystoisospora canis on hematological indicators of infested dogs with different indicators of invasion intensity - Suvorov, R.; Yevstafieva, V. (Scientific Progress & Innovations, 2025)
Cystoisospora canis are protozoan unicellular parasites that infect dogs. The reproductive stages, such as merogony and gametogony, occur in the gastrointestinal tract of animals, which causes characteristic clinical signs and changes in hematological parameters of infected dogs. The severity of such changes depends on many factors, one of which is the intensity of the invasion. The aim of the research was to determine the impact of the pathogen C. canis on the hematological indicators of infested dogs, taking into account the intensity of the invasion. The research was conducted in the conditions of the private veterinary clinic "Dovira" (Kharkiv) and the Laboratory of the Department of Parasitology and Veterinary and Sanitary Examination of the Poltava State Agrarian University (Poltava). Three groups of animals were formed, one of which was a control group (clinically healthy dogs) and two experimental groups (infested with cystoisospores at different invasion intensities – up to 500 oocysts/g and more than 500 oocysts/g). The content of hemoglobin, the number of erythrocytes, leukocytes, platelets and hematocrit were determined in the blood of dogs. During the experiment, it was found that the degree of negative impact of the cystoisosporosis pathogen on hematological parameters depended on the invasion intensity. At the intensity of cystoisosporosic invasion up to 500 oocysts/g in the blood of experimental dogs, the hemoglobin content, the number of erythrocytes, platelets and hematocrit index were slightly reduced. However, no significant deviations from similar indicators in clinically healthy animals were detected. At the same time, the number of leukocytes in the blood of experimental dogs significantly increased by 27.2 % compared to clinically healthy animals. With cystoisosporosic invasion intensity indicators of more than 500 oocysts/g in the blood of experimental dogs, a decrease in hemoglobin content by 20.4 %, in the number of erythrocytes by 30.4 %, in the hematocrit index by 28.7 %, and an increase in the number of leukocytes by 43.5 % were found compared to clinically healthy animals. The results of the conducted studies allow us to take into account changes in the blood of dogs depending on the intensity of cystoisosporosic invasion when prescribing complex treatment and increasing its effectiveness.